An assessment of brand awareness strategies used by Peace Security Company to enhance brand visibility - Mapingure, Brighton (Midlands State University, 2017)
This research sought to assess the effectiveness of brand awareness strategies that were implemented by Peace Security to enhance brand visibility. The study was motivated by intense competition in the security industry, stagnant market share growth and dominance of a few brands in an industry with over a 1500 registered security companies. Peace security has been in the security industry for more than a decade but remained little known compared to late entrants despite various brand awareness strategies in place. The major aims therefore were to ascertain the reasons for enhancing brand visibility at Peace security, the challenges faced in enhancing their brand visibility and determine other reasons besides brand awareness that influence choice of a security brand. The models that underpinned the study included the brand awareness dimension model showing different levels of brand visibility, brand identity prism for creating brand image, touchpoint model, spiral model and brand community theory which shows how customers develop awareness of a brand, understand it, associate with a brand and develop brand loyalty. A descriptive research approach was adopted in which questionnaires and interviews were used to collect both qualitative and quantifiable data. A target population of 96 was used which comprised of Peace security management, employees and clients in which a sample of 35% was used to ensure timely conclusion of the study and easier handling of information. The findings were presented using tables and analysed using descriptive statistics and content analysis. The findings revealed that the major reasons for enhancing brand visibility at Peace security were to increase market share, influence brand choice and increase marketing communication. They were facing several challenges, the major ones being costs, competition, absence of a branding department and brand loyalty. The major factors found to influence brand choice in the security industry included; price, service quality, legal compliance and track record or experience. The researcher concluded that the brand awareness strategies were not effective given challenges associated with the implementation and that some of their clients complemented the company services with those of its competitors. The researcher recommended that Peace Security Company should continue to enhance brand visibility, invest in their brand by establishing and operationalizing a branding department and strive to provide comprehensive security services through innovation and new security products development.